Clinical Masks of Neurofibromatosis Type 1 - R. N. Mustafin (SINAPS LLC, 2022)
Neurofibromatosis type 1 is the most common autosomal dominant tumor syndrome. The prevalence of the disease is 1 in 3000 people. Neurofibromatosis type 1 is characterized by the gradual appearance of signs of the disease and pronounced clinical polymorphism from erased and atypical forms to severe classical manifestations. The review is devoted to the consideration of diseases, the manifestations of which are significantly similar to neurofibromatosis type 1, and therefore, molecular diagnosis of the disease is an important method for differential diagnosis. To make a diagnosis of neurofibromatosis type 1, it is necessary to find mutations in the NF1 gene using sequencing. In 10% of cases, neurofibromatosis type 1 is caused by large deletions of the 17q11.2 locus, therefore, multiplex ligation-dependent probe amplification is also necessary. Typically, the initial manifestations of neurofibromatosis type 1 are multiple café-au-lait spots, which may be the only external signs of the disease for many years. Therefore, patients with neurofibromatosis type 1 may be mistakenly diagnosed with diseases for which these pigmentary changes are characteristic: Bloom, LEOPARD, Carney, Costello, Cowden, Legius, Nijmegen, Noonan, Peitz-Jägers, Silver-Russell, cardio-facio-cutaneous syndromes. The detection of subcutaneous tumors can become the basis for an incorrect diagnosis of the clinically similar Legius syndrome and multiple endocrine neoplasia. In addition, multiple lipomas are specific manifestations of Madelung or Dercum lipomatosis, familial angiolipomatosis, the etiology of which is considered unknown. Therefore, I assume that these diseases are atypical forms of neurofibromatosis type 1, since a number of authors have described the identification of mutations in NF1 gene in patients with multiple lipomatosis. Therefore, it is important to widely introduce into clinical practice the possibility of molecular genetic identification of the disease in order to identify cases of neurofibromatosis type 1 that do not meet the diagnostic criteria adopted by the NIH. It is promising to create a panel for the study of all genes, mutations in which can cause manifestations similar to neurofibromatosis. Early diagnosis of the disease is necessary for timely initiation of treatment and prevention of severe manifestations, since effective methods of antitumor therapy of neurofibromatosis type 1, such as inhibitors of mitogen-activated kinase, are being introduced into clinical practice.